A marking technique for intraoperative localization of small liver metastases before systemic chemotherapy - Zalinski, Stephanie (2009)
Preoperative chemotherapy is increasingly used prior to resection of colorectal liver metastases (CLM). Since some of these lesions may disappear or may be hardly detectable with intraoperative ultrasound (IOUS), we describe herein a new technique to mark small lesions with coils before chemotherapy. This technique facilitates the resection of small lesions likely to disappear after preoperative chemotherapy.